The Impact of Attractions, Amenity, and Accessibility on the Destination Image of Keraton Kanoman from the Perspective of Maqashid al-Syariah - Fatmasari, Dewi; Haryati, Yati (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
This study examines the impact of attractions, amenities, and accessibility, both partially and simultaneously, on the destination image of Keraton Kanoman Cirebon from the perspective of Maqashid Al-Syariah. A mixed-method approach was employed, utilizing questionnaires and multiple linear regression analysis. The population included tourists, market traders, tourism actors, local government representatives, and related agencies. The findings reveal that attractions and accessibility significantly impact the destination image, while amenities do not significantly affect it. Simultaneously, the three variables collectively contribute to shaping the destination image of Keraton Kanoman. Moreover, the management strategies implemented to enhance the destination image include organizing cultural and religious events such as the Nusantara Palace Festival, Panjang Jimat rituals, and celebrations of religious holidays. These efforts align with Maqashid Al-Syariah principles by promoting religious protection (hifz dien), intellectual enrichment (hifz aql), and economic empowerment (hifz al-maal). The study highlights the need for improved accessibility and the development of supporting amenities to further bolster the image of Keraton Kanoman as a heritage tourism destination.Keywords: Attractions, Accessibility, Destination Image, Maqashid Al-Syariah, Heritage Tourism.